2014
DOI: 10.1111/age.12182
|View full text |Cite
|
Sign up to set email alerts
|

Association between an alternative promoter polymorphism and sperm deformity rate is due to modulation of the expression of KATNAL1 transcripts in Chinese Holstein bulls

Abstract: Katanin p60 subunit A-like 1 (KATNAL1) is an ATPase that regulates Sertoli cell microtubule dynamics and sperm retention. We evaluated one novel splice variant and characterized the promoter and a functional single nucleotide polymorphism (SNP) of the bovine KATNAL1 gene to explore its expression pattern, possible regulatory mechanism and relationship with semen traits in Chinese Holstein bulls. A novel splice variant, KATNAL1 transcript variant 2 (KATNAL1-TV2) of the retained 68 bp in intron 2, was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Complementary DNA was synthesized using a transcript first-strand cDNA synthesis kit (TaKaRa, Dalian, China). The total RNA was extracted from tissues, and reverse transcription to cDNA was performed according to a previously published protocol [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementary DNA was synthesized using a transcript first-strand cDNA synthesis kit (TaKaRa, Dalian, China). The total RNA was extracted from tissues, and reverse transcription to cDNA was performed according to a previously published protocol [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the past, many similar works have been performed on goats [ 4 ] and boars [ 5 7 ]. However, only a few studies focused on the candidate marker genes in bulls [ 8 – 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, several studies point to KATNAL1 as a crucial gene for the spermatogenic process. 8,9 In the genetic association study performed by Fedick et al, 10 the KATNAL1 SNPs that showed the most promising trends towards association were rs17074420 (uncorrected p = 0.004, OR = 2.55) and rs17074416 (uncorrected p = 0.025, OR = 1.39), both of which are located in the 3′ end of the gene (specifically rs17074420 in the 3′UTR and rs17074416 at 3.5 kb downstream of KATNAL1). Interestingly, these SNPs are in LD (Dʹ > 0.8) with rs2149971, the tagger in the 3′ region of the gene that was analysed in our study (rs2149971-rs17074416 Dʹ = 0.85, rs2149971-rs17074420 Dʹ = 1.00, in the EUR population of the 1KGPh3).…”
Section: Discussionmentioning
confidence: 99%
“…8 Subsequent studies in bovine models also associated this abnormal phenotype with the presence of a splice variant of the gene that produces a loss of the microtubule interacting and trafficking domain resulting in KATNAL1 dysfunction. 9 Although the human KATNAL1 protein has a considerably high sequence identity with its bovine and murine orthologues (99% and 93%, respectively), no association of KATNAL1 genetic variants with human male infertility was observed in a case-control study performed by Fedick et al 10 However, some of the single-nucleotide polymorphisms (SNP) located in the 3′UTR of KATNAL1 were posited to predict male infertility based on a borderline statistical significance of the association, and the authors eventually speculated that these may have been because of limited statistical power, as only 105 non-obstructive azoospermia (NOA) cases and 242 normozoospermic controls were analysed. 10 Interestingly, genetic variants of the KATNAL2 and KATNB1 genes, which encode two additional members of the katanin family that interact with KATNAL1 to maintain the integrity of Sertoli cells and to allow the production of male germ cells, 11 have been associated with the development of male subfertility because of oligo-asthenoteratozoospermia, a condition characterised by low sperm counts, teratozoospermia (abnormal sperm shape) and asthenozoospermia (poor sperm movement).…”
Section: Introductionmentioning
confidence: 99%
“…; Zhang et al . ). In this study, we performed a genome‐wide association study (GWAS) for five semen traits of the bulls in Chinese Holstein to identify chromosome segments and genes with large effects on such traits.…”
Section: Descriptive Statistics Of the Deregressed And Original Estimmentioning
confidence: 97%